When to decide for transfusion in patients with liver cirrhosis and acute bleeding from esophageal varices? Liberal versus restrictive approach - Marušić, Marinko; Klemenčić, Antonio; Međugorac, Marin (AME Medical Journal, 2019)
Acute upper gastrointestinal (GI) bleeding is a common medical emergency that can result in life threatening haemorrhage and, therefore, it is associated with high risk of morbidity, mortality and high health care costs (1). Incidence of acute upper GI bleeding in the UK ranges between 100–150 per 100,000 adults annually, resulting in 70,000 hospital admissions every year (1). Upper GI hemorrhage represents one of the leading medical indication for blood transfusion, and accounts for 14% of all red blood cell (RBC) transfusions in England (2).